MULTI-COMMODITY NON-OIL EXPORT FORECASTING IN INDONESIA USING BACKPROPAGATION ARTIFICIAL NEURAL NETWORK - Suhermanto, Suhermanto; Siregar, Helmi Fauzi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Forecasting non-oil export commodities is critical for Indonesia's trade strategy, as these commodities contribute 93.8% of total national exports. This study develops a multi-commodity export prediction system using Artificial Neural Network (ANN) with backpropagation algorithm for 32 Indonesian non-oil commodities across six strategic sectors. Using monthly export data from February to August 2025 from Indonesia's Central Statistics Agency, we identified optimal neural network architecture 6-5-1 (6 input neurons for 6-month historical data, 5 hidden neurons, 1 output neuron). The model achieved 89.16% training accuracy and 88.43% testing accuracy with minimal 0.73% differential, indicating strong generalization without overfitting. Highest accuracy occurred on stable commodities (Tobacco: 99.94%, Animal/Plant Fats: 99.90%) while volatile commodities showed lower accuracy (Oil Seeds: 42.57%). The developed web-based system enables policymakers and exporters to make strategic decisions for international trade. This research demonstrates ANN backpropagation effectiveness for multi-dimensional commodity forecasting and provides practical decision-support tools for Indonesia's non-oil export sector.Keyword: artificial neural network; backpropagation; export forecasting; commodity prediction; Indonesia.Abstrak: Peramalan komoditas ekspor nonmigas sangat penting untuk strategi perdagangan Indonesia karena berkontribusi 93,8% dari total ekspor nasional. Penelitian ini mengembangkan sistem prediksi ekspor multi-komoditas menggunakan Jaringan Syaraf Tiruan (JST) dengan algoritma backpropagation untuk 32 komoditas nonmigas Indonesia di enam sektor strategis. Menggunakan data ekspor bulanan Februari-Agustus 2025 dari Badan Pusat Statistik Indonesia, kami mengidentifikasi arsitektur jaringan optimal 6-5-1 (6 neuron input untuk data 6 bulan, 5 neuron tersembunyi, 1 neuron output). Model mencapai akurasi training 89,16% dan testing 88,43% dengan diferensial minimal 0,73%, menunjukkan generalisasi kuat tanpa overfitting. Akurasi tertinggi pada komoditas stabil (Tembakau: 99,94%, Lemak dan Minyak: 99,90%) sedangkan komoditas volatil menunjukkan akurasi lebih rendah (Biji-bijian Berminyak: 42,57%). Sistem berbasis web memungkinkan pembuat kebijakan dan eksportir membuat keputusan strategis untuk perdagangan internasional. Penelitian ini menunjukkan efektivitas JST backpropagation untuk peramalan komoditas multi-dimensi dan menyediakan alat pengambilan keputusan praktis untuk sektor ekspor nonmigas Indonesia.Kata kunci: jaringan syaraf tiruan; backpropagation; peramalan ekspor; prediksi komoditas; Indonesia.